Reinforcement analyze and evaluate of higher-order thinking skills using problem-based learning in ecosystem material - Aulia Dhita Nanda; Rusdi Hasan; Akhmad Sukri; Marheny Lukitasari; Alice Tonido Rivera (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Higher-order thinking skills (HOTS) is one of the skills needed for 21st century challenges, especially for students. The aim of this study was to describe HOTS in students, especially the cognitive domain of analyzing and evaluating. This is a descriptive quantitative study employing a Pretest-Posttest One Group research design. The experiment was limited to 34 students heterogeneously from class X-C SMAN 1 Nglames. The research instruments used include learning observation sheets and posttests for student academic score also analyze and evaluate skills. The findings revealed that the average of analyze and evaluate of HOTS Completeness was 79.40% with a good category. The classical completeness of students in learning was 82.35% with a very complete category. Thus, the problem-based learning model can reinforce students' analysis(C4) and evaluate(C5) in higher order thinking skills of ecosystem material.